2019
DOI: 10.1111/jam.14158
|View full text |Cite
|
Sign up to set email alerts
|

Impact of triclosan adaptation on membrane properties, efflux and antimicrobial resistance of Escherichia coli clinical isolates

Abstract: Aim Analysing the effect of step‐wise exposure of Escherichia coli isolates to sublethal concentrations of triclosan (TCS) that is widely used as an antiseptic, preservative and disinfectant. Methods and Results Changes in the tolerance to the biocide itself and the cross‐resistance to clinically important antibiotics were analysed. The involvement of efflux mechanism was studied as well as the possible implication of modifications in cytoplasmic membrane properties including integrity, permeability, potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
8
28
0
Order By: Relevance
“…Under triclosan stimulation, increased efflux pump activity of the isolates were found in our study, and the expression levels of ABC transporters system encoding genes ydcT, ydcU, ydcV, ydcS, and cysU and RND-type tolc encoding genes acrB, acrD and yihV, as well as mdfA gene which belonging to MFS family had a significant increase compared with ATCC 25922, which were consistent with a previous study in China [23]. In contrast to previous studies we did not observed any increase in the expression levels of other efflux pump encoding genes as evidenced by Sonbol and Curiao et al [15,21], maybe it can be understood that ABC transport efflux pump, RND-type tolc and MFS family activity a stronger advantage than others during making adaptive changes of the studied isolates to triclosan [15,21]. All in all, we found that there was a strong relationship between gene overexpression and the increased tolerance of E. coli against triclosan, which suggested multiple efflux pumps may synergistically mediate triclosan resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Under triclosan stimulation, increased efflux pump activity of the isolates were found in our study, and the expression levels of ABC transporters system encoding genes ydcT, ydcU, ydcV, ydcS, and cysU and RND-type tolc encoding genes acrB, acrD and yihV, as well as mdfA gene which belonging to MFS family had a significant increase compared with ATCC 25922, which were consistent with a previous study in China [23]. In contrast to previous studies we did not observed any increase in the expression levels of other efflux pump encoding genes as evidenced by Sonbol and Curiao et al [15,21], maybe it can be understood that ABC transport efflux pump, RND-type tolc and MFS family activity a stronger advantage than others during making adaptive changes of the studied isolates to triclosan [15,21]. All in all, we found that there was a strong relationship between gene overexpression and the increased tolerance of E. coli against triclosan, which suggested multiple efflux pumps may synergistically mediate triclosan resistance.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 200 E. coli isolates were collected from patients with UTIs, and only five triclosanresistant strains (2.5%, 5/200) were selected, the rate of which was lower than the previous report [19]. These triclosan-resistant strains, rather than susceptible strains, were characterized by a MDR profiles, we supposed that there may be a cross-resistance between triclosan and antibiotics in E. coli based on previous studies [20,21].…”
Section: Discussionmentioning
confidence: 89%
“…Under triclosan stimulation, increased efflux pump activity of the isolates were found in our study, and the expression levels of ABC transporters system encoding genes ydcT, ydcU, ydcV, ydcS, and cysU and RND-type tolc encoding genes acrB, acrD and yihV, as well as mdfA gene which belonging to MFS family had a significant increase compared with ATCC 25922, which were consistent with a previous study in China [29]. In contrast to previous studies, we did not observed any increase in the expression levels of other efflux pump encoding genes, maybe it can be understood that ABC transport efflux pump, RND-type tolc and MFS family activity a stronger advantage than others during making adaptive changes of the studied isolates to triclosan [17,22].…”
Section: Discussionsupporting
confidence: 90%
“…Based on the obtained phenomena and previous reports, we thought that the emergence or evolution of multiple or cross-resistance is related to the exposure time of triclosan, which provided a sufficient evidence for clinical practice to avoid long-term use of triclosan [22,26]. Moreover, it is worth noting that significantly reduced triclosan sensitivity was found by serial passage experiment, which provided a beneficial guidance for reasonable use of triclosan, including concentration and dosage, in order to prevent the increase resistance of pathogens to triclosan.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation